2013
DOI: 10.1111/bph.12000
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline stimulates cell proliferation by suppressing potassium channels via Gi/o‐protein‐coupled α1B‐adrenoceptors in human osteoblasts

Abstract: BACKGROUND AND PURPOSERecent studies demonstrated that the sympathetic nervous system regulates bone metabolism via b2-adrenoceptors. Although a-adrenoceptors are also expressed in osteogenic cells, their functions in bone metabolism have been less studied. We previously demonstrated that noradrenaline suppressed potassium currents via a1B-adrenoceptors in the human osteoblast SaM-1 cell line. The aim of this study was to investigate the signal transduction pathway and the physiological role of noradrenaline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…The physiological action of adrenaline (epinephrine) was previously demonstrated to be mediated by α 1 ‐ as well as ß‐ adrenoceptor signalling in osteoblasts. Our previous studies also showed that cellular proliferation was facilitated via α 1B ‐ adrenoceptors and inhibited via ß‐ adrenoceptors in human osteoblastic SaM‐1 cells (Kodama & Togari, ). In the present study, phenylephrine stimulated chloroethylclonidine, cellular proliferation on BMSCs (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The physiological action of adrenaline (epinephrine) was previously demonstrated to be mediated by α 1 ‐ as well as ß‐ adrenoceptor signalling in osteoblasts. Our previous studies also showed that cellular proliferation was facilitated via α 1B ‐ adrenoceptors and inhibited via ß‐ adrenoceptors in human osteoblastic SaM‐1 cells (Kodama & Togari, ). In the present study, phenylephrine stimulated chloroethylclonidine, cellular proliferation on BMSCs (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 78%
“…α 1 ‐Adrenoceptors were previously shown to have an important role in regulating the functionality of osteoblasts (Suzuki et al, ; Huang et al, ; Hirai et al, ). We also reported direct nerve‐osteoblast communication in vitro and demonstrated that NA increased cell proliferation by suppressing K + channels via Gi/o‐coupled α 1B ‐adrenoceptors in human osteoblasts (Obata et al, ; Kodama & Togari, ); however, the physiological role of α 1 ‐adrenoceptor signalling in bone in vivo remains unclear. Thus, to obtain a deeper understanding of bone remodelling by the sympathetic nervous system, we investigated the role of α 1 ‐adrenoceptor signalling in bone metabolism.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…It has been shown that norepinephrine (NE), a major mediator of the sympathetic nervous system, influences osteoblasts both in culture and in vivo [19][22]. NE has also been demonstrated to stimulate osteoclast formation, thereby enhancing bone resorption [19].…”
Section: Introductionmentioning
confidence: 99%